Dialektika Politik dan Agama Kerajaan Bima Tahun 1775-1882: Kesaksian Naskah Bo' Bumi Luma Rasanae, Sepuluh Surat Sultan Bima Abdul Hamid Muhammad Syah dan Jawharat al-Ma'arif - Firdausy, Hilmy (Faculty of Islam Nusantara, Nahdlatul Ulama University of Indonesia (Unusia) Jakarta., 2023)
Not much effort has been made to explore Bima as a historical node within the framework of Islamic epistemology in Nusantara. In fact, the area that was formerly known as the Bima Kingdom became one of the important trading ports that connected the spice shipping routes to the east of the Nusantara. Because of its strategic location and its significance in the connection point of spice shipping in the Nusantara, Bima in the end can not only be read as an economic reality, but also a cultural reality which is a reflection, for example, how religion and politics are dialectic and bargain each other. The book